Overutilization of Radiographs for Pulled Elbow Among Orthopedic Surgeons Compared With Pediatricians. Issue 12 (22nd December 2022) - Kadar, Assaf; Yaniv, Noga; Warschawski, Yaniv; Rosenthal, Yoav; Shemesh, Shai; Weigl, Daniel; Frenkel Rutenberg, Tal
Background: Pulled elbow is a common pediatric condition, treated by pediatricians and orthopedic surgeons. The diagnosis is clinical, and imaging is only required where an occult fracture is suspected, although overuse is reported. In this study, we explore the epidemiology of pulled elbow in Israel, focusing on the differences in management between physicians of various specialties. Methods: Electronic medical records of the largest health provider in Israel, which provides health services to more than 50% of the population, were reviewed for pulled elbow cases between 2005 and 2020. Patients aged 4.5 months to 7 years were included. Demographic information, the discipline of the treating physician, and acquisition of elbow radiographs were gathered. Results: A total of 4357 patients, 62.8% girls, were included. The average body mass index was 16.1 (SD, 1.2). Most patients were from communities in the upper half of the socioeconomic status clusters 6 to 10 (64.63%). Most patients were attended by a pediatrician (51.5%), followed by an orthopedic surgeon (19.9%). Radiographs were acquired for 570 children (13.1%). Most radiographs (36.5%) were requested by orthopedic surgeons and for children in the boundary age groups. The patient's socioeconomic status was associated with access to physicians of different subspecialties, and lower income families had a higher tendency to be treated by nonspecialized physician ( P < 0.001). Conclusions: Orthopedic surgeons use elbow radiographs much more than pediatricians; effort should aim at reducing the imaging rate for this population.